Evaluating the Efficacy of Povidone-Iodine Solution Infection Prophylaxis in Immediate Tissue Expander-Based Breast Reconstruction: A Controlled Retrospective Analysis. Issue 1 (February 2023) - Teotia, Sumeet S.; Kadakia, Yash; Amaya, Joshua; Liu, Yulun; Haddock, Nicholas T.
Background: There is currently no consensus among plastic surgeons regarding the optimal infection prophylaxis for immediate tissue expander placement following mastectomy. The goal of this study was to determine whether irrigation with 1 L of standard triple antibiotic solution (TAS) can achieve similar infection rates compared to a regimen of 180 mL of TAS with povidone-iodine solution (Betadine) painted on the field immediately prior to the placement of the expander.Methods: The 2 regimens were compared via retrospective propensity matching of all patients of the 2 senior authors who underwent bilateral tissue expander placement immediately following mastectomy with one of 3 mastectomy surgeons from January 2013 to December 2019 (n = 281). Groups were controlled for mastectomy surgeon, mastectomy type, mastectomy weight, age, race, body mass index, diabetes, hypertension, smoking, smoking status, prepectoral/subpectoral placement, use of acellular dermal matrix, operating room time, and duration of postoperative antibiotics.Results: Compared to the Betadine cohort (n = 65), the non-Betadine cohort (n = 65) experienced a similar rate of infections (13.8% vs 12.3%, P = 1.00), including major injections requiring intravenous antibiotic treatment (10.8% vs 9.2%, P = 1.00), after propensity matching. Infections in the non-Betadine cohort did not grow different bacteria on culture, require different antibiotic coverage, or result in prolonged duration of average antibiotic therapy (12.0 days vs 19.3 days, P = .19). Rates of subsequent expander washout and exchange ( P = 1.00) and overall complications that required return to the operating room ( P = .826) were similar between groups.Conclusion: The addition of Betadine solution to TAS added no benefit to infection prophylaxis or reduction of surgical complications in immediate tissue expander placement procedures.